Respostas

A melhor resposta!
2014-05-18T22:31:05-03:00
Esta sequência forma uma progressão aritmética:
a1 = ?
a2 = 4
a3 = 6

r = a3 - a2 = 6 - 4 = 2
Logo, a1 = 2

S(n) = (a1 + an) n /2 = 72

(a1 + an) n /2 = 72

(a1 + an) n = 144

an = a1 + (n-1)r
an = 2 + 2(n-1) = 2n

Voltando à soma:
(2 + 2n) n = 144
2n + 2n² = 144
n² + n - 72 = 0
delta = raiz(1 + 288) = raiz(289) = 13

n1 = (- 1 + 17) / 2 = 16/2 = 8

n2 = (-1 - 17) / 2 = - 9 (Negativo não conta)

Resposta: 8 dias
1 5 1
2014-05-18T22:46:37-03:00